A biomechatronical transtibial prosthesis powered by pleated pneumatic artificial muscles. (1st December 2008) - Versluys, Rino; Desomer, Anja; Lenaerts, Gerlinde; Pareit, Olivier; Vanderborght, Bram; Perre, Georges; Peeraer, Louis; Lefeber, Dirk
Due to its high power-to-weight ratio, a pleated pneumatic artificial muscle (PPAM) offers an interesting alternative actuation source for robotic devices. Its inherent compliant behaviour excites another broad field of interest: assistive clinical devices such as powered exoskeletons and prosthetics. In this paper, the design of a pneumatically powered transtibial prosthetic device is presented. A first prototype has been built and provides a preliminary test bed for control algorithm development and testing with able-bodied subjects in laboratory conditions. The characteristics and working principle of a PPAM are described. The design specifications and the mechanical model of the prosthesis are discussed. The mechanical design and the control structure are outlined. Furthermore, some initial walking trials with an able-bodied subject wearing the prosthesis prototype are presented and discussed.